Study the antibacterial activity of probiotics against uropathogenic (E. coli) of chronic kidney disease patients - Maryam Adnan Mohsin; Sanaa Khudhur Jameel (مجلة علوم ذي قار)
Chronic kidney disease (CKD) is a gradual decline of kidneys that results in kidney failure. This disease compromises the body's immune system, elevating susceptibility to infections. One of the serious risk factors for CKD is urinary tract infections (UTIs), which may also be the most common infectious disease associated with CKD patients. Recently, antibiotic resistance has become the biggest problem facing specialists in the field of treating infections; thus, probiotics could be an alternative solution for fighting pathogenic attacks, especially bacterial ones. This study aimed to investigate the antibacterial activity of probiotic effect against CKD-isolateduropathogenic Escherichia coli (E. coli) . From October 2023 to April 2024, 300 urine samples were collected from patients aged ≥ 18 years with suspected chronic kidney disease (CKD), and only 44 of the urine samples gave positive results for cultures. Uropathogenic (E.col) isolates which were double diagnosed by vitek-2 system showed almost high resistance results to 16 used antibiotics, and it showed that Ampicillin, Cefuroxime, and Cefurxime Axetil had the highest resistance results. The biofilm formation profile for 44 tested isolates showed 0% of non-formation, 0% of weak formation, 45.4% of moderate formation, and 54.6% of strong formation respectively. It was detected that only the bacteriocin concentrations of 125×103 µg/ml and 62.500 µg/ml showed the minimum inhibitory concentrations (MICs) for highly resistant bacterial isolates, and the broth microdilution method (BMD) was the best choice for this detection.